2022
DOI: 10.3390/genes13010104
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disordered Breathing, Obesity and Atrial Fibrillation: A Mendelian Randomisation Study

Abstract: It remains unclear whether the association between obstructive sleep apnoea (OSA), a form of sleep-disordered breathing (SDB), and atrial fibrillation (AF) is causal or mediated by shared co-morbidities such as obesity. Existing observational studies are conflicting and limited by confounding and reverse causality. We performed Mendelian randomisation (MR) to investigate the causal relationships between SDB, body mass index (BMI) and AF. Single-nucleotide polymorphisms associated with SDB (n = 29) and BMI (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…Nevertheless, a Mendelian randomisation study of data from 55 114 patients with AF and 482 295 controls, published in 2022, showed that sleep disordered breathing was not associated with AF after adjusting for body mass index. 30 Importantly, however, body mass index remained associated with AF after adjusting for obstructive sleep apnoea. This finding suggests that the link between obstructive sleep apnoea and AF might be mediated or confounded by concurrent obesity in patients with mild-to-moderate obstructive sleep apnoea 30 and supports aggressive strategies for weight reduction to mitigate AF risk in these patients.…”
Section: Continuous Positive Airway Pressurementioning
confidence: 95%
See 3 more Smart Citations
“…Nevertheless, a Mendelian randomisation study of data from 55 114 patients with AF and 482 295 controls, published in 2022, showed that sleep disordered breathing was not associated with AF after adjusting for body mass index. 30 Importantly, however, body mass index remained associated with AF after adjusting for obstructive sleep apnoea. This finding suggests that the link between obstructive sleep apnoea and AF might be mediated or confounded by concurrent obesity in patients with mild-to-moderate obstructive sleep apnoea 30 and supports aggressive strategies for weight reduction to mitigate AF risk in these patients.…”
Section: Continuous Positive Airway Pressurementioning
confidence: 95%
“…30 Importantly, however, body mass index remained associated with AF after adjusting for obstructive sleep apnoea. This finding suggests that the link between obstructive sleep apnoea and AF might be mediated or confounded by concurrent obesity in patients with mild-to-moderate obstructive sleep apnoea 30 and supports aggressive strategies for weight reduction to mitigate AF risk in these patients.…”
Section: Continuous Positive Airway Pressurementioning
confidence: 95%
See 2 more Smart Citations
“…There is accumulating evidence that sleep dysfunction promotes in ammatory responses in brain and peripheral tissues, which can contribute to the development of chronic pathologies, such as metabolic and cardiovascular diseases and neurological disorders [1][2][3]. The global increase in obesity rates has led to a pronounced rise in the incidence of obstructive sleep apnea [4]. Chronic sleep fragmentation (SF) simulates the interrupted sleep experienced by patients with obstructive sleep apnea and other sleep disorders [5][6][7].…”
Section: Introductionmentioning
confidence: 99%